Geographical and experimental contexts modulate the effect of warming on top‐down control: a meta‐analysis. (24th January 2018) - Marino, Nicholas dos Anjos Cristiano; Romero, Gustavo Quevedo; Farjalla, Vinicius Fortes
Abstract: Ecologists have extensively investigated the effect of warming on consumer–resource interactions, with experiments revealing that warming can strengthen, weaken or have no net effect on top‐down control of resources. These experiments have inspired a body of theoretical work to explain the variation in the effect of warming on top‐down control. However, there has been no quantitative attempt to reconcile theory with outcomes from empirical studies. To address the gap between theory and experiment, we performed a meta‐analysis to examine the combined effect of experimental warming and top‐down control on resource biomass and determined potential sources of variation across experiments. We show that differences in experimental outcomes are related to systematic variation in the geographical distribution of studies. Specifically, warming strengthened top‐down control when experiments were conducted in colder regions, but had the opposite effect in warmer regions. Furthermore, we found that differences in the thermoregulation strategy of the consumer and openness of experimental arenas to dispersal can contribute to some deviation from the overall geographical pattern. These results reconcile empirical findings and support the expectation of geographical variation in the response of consumer–resource interactions to warming.